Long-Term Social Human-Robot Interaction for Neurorehabilitation: Robots as a Tool to Support Gait Therapy in the Pandemic - Céspedes, Nathalia; Raigoso, Denniss; Múnera, Marcela; Cifuentes, Carlos A. (Western University, 2021)
COVID-19 pandemic has affected the population worldwide, evidencing new challenges and opportunities for several kinds of emergent and existing technologies. Social Assistive Robotics could be a potential tool to support clinical care areas, promoting physical distancing, and reducing the contagion rate. In this context, this paper presents a long-term evaluation of a social robotic platform for gait neurorehabilitation. The robot’s primary roles are monitoring physiological progress and promoting social interaction with human distancing during the sessions. A clinical validation with ten patients during 15 sessions were conducted in a rehabilitation center located in Colombia. Results showed that the robot’s support improves the patients’ physiological progress by reducing their unhealthy spinal posture time, with positive acceptance. 65% of patients described the platform as helpful and secure. Regarding the robot’s role within the therapy, the health care staff agreed (>95%) that this tool can promote physical distancing and it is highly useful to support neurorehabilitation throughout the pandemic. These outcomes suggest the benefits of this tool to be further implemented in the pandemic.

La pandemia de COVID-19 ha afectado a la población mundial, evidenciando nuevos retos y oportunidades para varios tipos de tecnologías emergentes y existentes. La robótica social de asistencia podría ser una herramienta potencial para apoyar las áreas de atención clínica, promoviendo el distanciamiento físico y reduciendo la tasa de contagio. En este contexto, este artículo presenta una evaluación a largo plazo de una plataforma robótica social para la neurorrehabilitación de la marcha. Las funciones principales del robot son monitorear el progreso fisiológico y promover la interacción social con distanciamiento humano durante las sesiones. Se realizó una validación clínica con diez pacientes durante 15 sesiones en un centro de rehabilitación ubicado en Colombia. Los resultados mostraron que el apoyo del robot mejora el progreso fisiológico de los pacientes al reducir el tiempo de postura espinal no saludable, con una aceptación positiva. El 65% de los pacientes describieron la plataforma como útil y segura. En cuanto al papel del robot en la terapia, el personal sanitario estuvo de acuerdo (>95 %) en que esta herramienta puede promover el distanciamiento físico y es muy útil para apoyar la neurorrehabilitación durante la pandemia. Estos resultados sugieren que es beneficioso implementar esta herramienta en mayor medida durante la pandemia.
Keywords: Robótica médica; Robotics in medicine; Tecnología médica; Medical technology; Rehabilitación médica; Medical rehabilitation; COVID-19; Rehabilitación de la marcha; Gait rehabilitation; Lokomat; Interacción humano-robot a largo plazo; Long-term human-robot interaction; Biorretroalimentación; Biofeedback; Robótica de asistencia social; Socially assistive robotics